Effect of ozone irrigation and powered toothbrushing on dental plaque, gingival inflammation, and microbial status in institutionalized mentally challenged individuals: A double-blinded, randomized, controlled clinical trial - Pramod Vinayak Tatuskar; Shaswata Karmakar; Narayan Narendra Walavalkar; Kharidhi Laxman Vandana (Wolters Kluwer Medknow Publications, 2023)
Aim: This study compares and evaluates the efficacy of ozonated water irrigation (OZI) and powered toothbrushing on the oral health and microbial status of mentally challenged individuals. Materials and Methods: Thirty individuals of age range 15-30 years with a mild-to-moderate level of mental retardation (MR) and gingival inflammation participated in this double-blind randomized controlled clinical trial. Total duration of the study was 45 days consisting of two clinical phases (phase I, i.e., aided) and phase II, i.e. unaided) of the duration of 21 days in each phase, with a washout period of 3 days between the two phases. With a split-mouth design, sites from each subject were randomly allocated into two treatment groups: Powered Toothbrushing (PB) and OZI were randomly done for each half side of the mouth of each subject. Subgingival plaque samples were collected from sites of both the treatment groups and sent for microbial analysis. Clinical and microbial parameters were measured before and after the treatment. Results: Significant improvement of the clinical and microbial parameters was found in both treatment groups. However, intergroup differences in the parameters were statistically nonsignificant. Conclusion: OZI could serve as an alternative or adjunct to powered toothbrushes for people with MR.